2013
DOI: 10.1007/s13277-013-0728-9
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory mechanism of CCR7 gene expression and its involvement in the metastasis and progression of gastric cancer

Abstract: Gastric cancer is the second leading cause of cancer mortality, but the molecular mechanisms underlying its progression and metastasis remain unclear. CCR7 and Dicer 1 protein expression in 80 gastric adenocarcinomas and 40 peritumoral tissues were measured by immunohistochemical staining. The expression of let-7a miRNA in serum, tumor tissues, and peritumoral tissues was measured by real-time PCR. The role of let-7a in CCR7 protein expression, migration, and invasion of gastric cancer cells was tested in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Numerous studies have shown that CCR7 is differentially expressed in tumor cells in gastric cancer at the mRNA and protein levels, as well as in the cell membrane in vitro and in vivo (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). In addition, CCR7 was detected in tumor-infiltrating lymphocytes and dendritic cells in gastric cancer, as well as in mononuclear cells in Helicobacter pylori gastritis (35,38).…”
Section: C-c Motif Ccr7mentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that CCR7 is differentially expressed in tumor cells in gastric cancer at the mRNA and protein levels, as well as in the cell membrane in vitro and in vivo (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). In addition, CCR7 was detected in tumor-infiltrating lymphocytes and dendritic cells in gastric cancer, as well as in mononuclear cells in Helicobacter pylori gastritis (35,38).…”
Section: C-c Motif Ccr7mentioning
confidence: 99%
“…In addition, H. pylori upregulated CCR7 in CCR7-expressing gastric cancer cell lines, whereas no difference in CCR7 upregulation was identified between the cag + and cag -H. pylori strains (35,39,40). Wang et al (32) demonstrated that CCR7 protein expression was significantly higher in gastric cancer compared with peritumoral tissues, and that high levels of CCR7 expression could be induced by loss of Dicer-1 and decreased levels of let-7a microRNA (miRNA) in gastric cancer. In that study, transfection of let-7a miRNA into gastric cancer cells markedly inhibited the expression of functional CCR7, suggesting that miRNA is involved in the regulation of CCR7 expression (32).…”
Section: C-c Motif Ccr7mentioning
confidence: 99%
See 1 more Smart Citation
“…After excluding irrelevant articles by reviewing the titles and abstracts of those studies, two investigators (P. Du and Y. Liu) reviewed the full text version of the remaining 30 articles independently in accordance with the inclusion and exclusion criteria. Finally, 15 articles [7][8][9][10][13][14][15][16][17][18][19][20][21][22][23] comprising data on 1697 participants met the requirement of the analysis. The detailed search steps are described in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…The CC chemokine CCL19 and its receptor CCR7, which regulate chemotaxis and the transendothelial migration of leukocytes during immune and inflammatory reactions, were recently observed to play an important role in the metastasis of various types of cancer [25]. We have also reported that CCR7 regulates cell migration and adhesion in metastatic squamous cell carcinoma of the head and neck by activating integrin, PI3K/cdc42, pyk2, and Src [615].…”
Section: Introductionmentioning
confidence: 99%